Rethinking Critical Editions of Fragmentary Texts By Ontologies - Romanello, Matteo; Boschetti, Federico; Berti, Monica; Babeu, Alison; Crane, Gregory (Tufts Archival Research Center, 2005)
This paper discusses the main issues encountered in the design of a domain ontology to represent ancient literary texts that survive only in fragments, i.e. through quotations embedded in other texts. The design approach presented in the paper combines a knowledge domain analysis conducted through semantic spaces with the integration of well established ontologies and the application of ontology design patterns. After briefly describing the specific meaning of "fragment" in a literary context, the paper gives insights into the main conceptual issues of the ontology design process. Lastly, it outlines the overall architecture of protocols, services and data repositories which is required to implement a digital edition of fragments based on the proposed ontology.